Towards an Examination of Error Related Neural Processes in Real-World Tasks: ERP Evidence of Uncertainty, Expectancy, Difficulty and Anxiety - Stewart, Peter C. (My University, 2009)
﻿In four experiments I addressed factors that affect human performance monitoring as indicated by neural correlates observed in response-locked event related potentials. Specifically, I examined modulations of the error related negativity (ERN), the correct response negativity (CRN), and the error positivity (Pe) components across a variety of conditions. These components, all thought to be generated in the anterior cingulate cortex, represent activation of the performance monitoring system. Experiments 1 and 2 used stimulus congruency and visual noise to manipulate response and stimulus uncertainty in an extension of previous research. These manipulations, together with a between experiment task manipulation, examined the role of cognitive/attentional load in performance monitoring. Replication of previous findings and a task specific modulation of ERN amplitudes provided support for a role of cognitive load in performance monitoring. Further, these two experiments used a novel task and novel stimuli to replicate previous research and extend our knowledge of how uncertainty affects performance monitoring. In stark comparison to all previous research in this area, Experiments 3 and 4 both employed complex and somewhat ecologically valid tasks. Standard ERN/Pe results in Experiment 3 (touch typing task) revealed that it is possible to examine the ERN in more complex, real world-like tasks. Further, an expectancy manipulation elicited marginal differences in the response-locked Pe but resulted in large N1 and P3 differences suggesting a possible role of attention in early expectation driven performance monitoring adjustments. Experiment 4 examined the role of task difficulty, anxiety level and exposure (i.e., time on task) for effects on ERN and Pe amplitudes. By comparing how math anxious people perform in a math environment, this study represents the first to pit a specific anxiety against a specific anxiety provoking situation. This complex paradigm again replicated general ERN findings providing further support for the validity of complex task usage. Findings surrounding the difficulty manipulation and anxiety measures provide new insight into the role of difficulty in performance monitoring and support the importance of considering personality characteristics in self-regulation.
Keywords: human, performance, neural, ERN, CRN, visual, anxiety